2012
DOI: 10.1016/j.diff.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of atrial and atrioventricular septal defects with special emphasis on the role of the dorsal mesenchymal protrusion

Abstract: Partitioning of the four-chambered heart requires the proper formation, interaction and fusion of several mesenchymal tissues derived from different precursor populations that together form the atrioventricular mesenchymal complex. This includes the major endocardial cushions and the mesenchymal cap of the septum primum, which are of endocardial origin, and the dorsal mesenchymal protrusion (DMP), which is derived from the Second Heart Field. Failure of these structures to develop and/or fully mature results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 167 publications
2
115
0
3
Order By: Relevance
“…The implication of Tbx5 and Osr1 interaction in the SHF for atrioventricular septation buttresses our previous implication of Tbx5 and a growing body of literature indicating that SHF defects can cause AVSDs [10, 11, 23, 49-51]. In the present report, we showed an increased incidence of primum AVSDs in Tbx5 and Osr1 compound heterozygotes (Figure 3), a result that confirmed the interaction between Tbx5 and Osr1 in the pSHF for atrial septation.…”
Section: Discussionsupporting
confidence: 90%
“…The implication of Tbx5 and Osr1 interaction in the SHF for atrioventricular septation buttresses our previous implication of Tbx5 and a growing body of literature indicating that SHF defects can cause AVSDs [10, 11, 23, 49-51]. In the present report, we showed an increased incidence of primum AVSDs in Tbx5 and Osr1 compound heterozygotes (Figure 3), a result that confirmed the interaction between Tbx5 and Osr1 in the pSHF for atrial septation.…”
Section: Discussionsupporting
confidence: 90%
“…In response to their comments, our replies are as follows. The anatomical identity of the derivatives of dorsal mesenchymal protrusion (DMP) in our studies is in agreement with that described previously (2-5), which can be mapped by Mef2c-AHF-Cre (3,5), and was also shown to be overlapped with Shox2 expression (2). We also found that Shox2 is co-expressed with Hcn4, Nkx2-5, and cTnT in the DMP derivatives at E11.0 ( Fig.…”
Section: This Is a Response To A Letter By Kelder Et Al (1)supporting
confidence: 80%
“…AP1 proteins regulate a variety of processes including cell proliferation and survival, differentiation, growth, migration, and transformation. Intriguingly, conditional deletion of the AP1 family member Jun using Tie2-Cre leads to DORV, VSDs, and valve defects (54), suggesting that perhaps JUN cooperates with TBX20 in endocardial lineages to effect ture required for proper atrioventricular septation (13,53). Notably, this defect was not observed in our analysis of Nfatc1-Cre Tbx20 fl/fl mutants.…”
Section: Tbx20 Regulates the Endocardial Proliferation And Migratory mentioning
confidence: 37%